Acoustic Doppler Current Profiling for streamflow measurements in subarctic climate - Nyström, Linus (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2022)
The ADCP (Acoustic Doppler Current Profiling) technology has been widely available and acknowledged as an instrument used for different types of flow measurement since 1990s, from small scale river measurements to larger ocean current mappings. This study was conducted by the author in cooperation with SWECO with the focus on smaller scale measurements especially on small natural watercourses in a sub-arctic climate with the purpose to examine if the ADCP technology can be used as a complement to the more classic methods for this type of flow measurements Current meter and Conductivity flow measurements. To achieve the scope of the study a total of eight field excursions for data gathering on a total of four different watercourses was performed during the winter and spring season to be able to compare different types of flows. Literature studies and information gathering on the technology as well as previous studies on the subject was conducted throughout the period of the study, with a special focus around the Streampro implementation of the technology adapted for stream flow measurements on a smaller scale. During the early field excursions, it was realized that measurements using theADCP-technology during the winter was difficult due to thick icesheets on the watercourses as well as a low particle content in the water column which resulted in a high uncertainty in the data as well as in some cases unable to perform measurements that could be considered representative for the actual flow especially on the shallowest locations but also for the deeper watercourses examined in the report. The results showed that during the spring season from April to May the consistency in the data got substantially better resulting in a lower uncertainty and a higher precision in the data, in many cases a precision higher than the more classic methods of flow measurements. It was also realized during the study that to gain a better knowledge of the applicability of the technology in this field a similar study would have to be ...